Case report: cerebellar hypoplasia associated with bovine viral diarrhoea (BVD) virus infection in a calf, in Turkey - Gul, Y.; Issi, M.; Cevik, A.; Gurcay, M.; Baydar, E.; Eroksuz, H. (Ecole Nationale Veterinaire Toulouse, 2013)
This is the first published report of cerebellar hypoplasia associated with bovine viral diarrhoea (BVD) virus infection in a calf from the Elazig province, Turkey. A 3-weeks old female Holstein calf was unable to stand with its head pulled backwards and opisthotonos. As cerebellar hypoplasia was evoked, euthanasia and necropsy were performed. Numerous severe cavities were found in cerebellum; folial structures were hypoplastic (cell depletion in the external granular layer, disappearance of white matter in some foliae, and loss of Purkinje cells) and the diagnosis of cerebellar hypoplasia was confirmed. Additionally, nodular costochondral lesions were observed and tissue homogenates gave positive results with specific ELISA test and RT-PCR for the BVD virus. These results show that the BVD virus infection can cause cerebellar hypoplasia and this association may be included in the differential diagnosis with cerebrocortical necrosis, hypovitaminosis A and encephalitic colibacillosis in calves.
Keywords: calf; cerebellar hypoplasia; bovine viral diarrhoea; virus antigen; RT-PCR; Turkey